2017
DOI: 10.5468/ogs.2017.60.1.100
|View full text |Cite
|
Sign up to set email alerts
|

Effect of calcium on premenstrual syndrome: A double-blind randomized clinical trial

Abstract: ObjectivePremenstrual syndrome (PMS) affects millions of women and is known as the most important disorder among them. The very aim of the present study was to evaluate the effects of low dose calcium on severity of PMS.MethodsThis study can be considered as a double-blind randomized clinical trial. Female students of Hamadan University of Medical Sciences diagnosed with PMS in 2014 participated in the present study. Sixty-six female students diagnosed with PMS were involved in the experimental and control gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 11 publications
0
21
0
5
Order By: Relevance
“…Additionally, complementary therapies, including nutritional supplementation with calcium, vitamin D or B 6 [15], and herbal supplements [e.g. St John’s wort, vitex agnus-castus; 16], are being used, although sufficient evidence is currently lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, complementary therapies, including nutritional supplementation with calcium, vitamin D or B 6 [15], and herbal supplements [e.g. St John’s wort, vitex agnus-castus; 16], are being used, although sufficient evidence is currently lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with oral contraceptives in patients containing drospirenone significantly decreased PMS and PMDD symptomatology [27], but other studies have found a less robust effect on PMDD [4]. As previously mentioned, calcium and vitamin D supplementation have also been shown to decrease symptoms of PMS and PMDD; however, such supplementation appears to be much more effective for reducing PMS symptoms than those of PMDD [1,24]. Finally, lifestyle changes such as exercise, meditation, decreasing caffeine consumption, and stress management can be effective in decreasing the severity of symptoms in PMS and, to a lesser extent, PMDD [20].…”
Section: Treatment For Premenstrual Distress and Suicidalitymentioning
confidence: 99%
“…These include the effects of exercise, the importance of the gut microbiome, increased intake of anti-oxidants in foods and supplements, low sugar consumption and increased intake of probiotics, vitamins and supplements such as curcumin, B vitamins, calcium, ginger, omega3 and melatonin. [44][45][46][47][48][49][50][51]…”
Section: The Role Of Stressmentioning
confidence: 99%